IMPLEMENTASI SISTEM MONITORING PROYEK DI CV.INFOKOMUNIKASI KUDUS BERBASIS WEB - Sumardi Sumardi (AMIK Jakarta Teknologi Cipta Semarang, 2014)
Information technology, media sending and receiving information has allowed both government and private agencies in all fields of use. As with the CV. Infokomunikasi Kudus is using information technology. To improve performance in terms of repairs and the addition of the required information technology services that can be packed in a distributed project management process. Monitoring and supervision of progress of the project administration is required by all relevant units quickly, realtime and accurate. Initially the storage, recording and dissemination of project information is done manually with the help of an excel worksheet application. Manufacture of engineering innovation project monitoring system is needed to give solution existing conditions. Design of the project monitoring system is made according to the conditions and needs in the field. Implementation of the project monitoring system design is built with PHP as a programming language to create the user interface, and MySQL as database server. MySQL database to store the project data has been entered by the user. While PHP itself serves to create a web application that displays the contents of the database Keywords : project monitoring, application, design, database, web